2017
DOI: 10.1016/j.jsxm.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Prophylactic Gentamicin During Penile Prosthesis Surgery: A Retrospective Comparison of Two Different Doses

Abstract: Background Gentamicin has been determined to be active against a wide range of bacterial infections and has been commonly used as a preoperative antibiotic for inflatable penile prosthesis (IPP) implantation. However, the best dosing regimen to produce the safest optimal prophylactic effect remains to be determined. Aim To compare low- and high-dose gentamicin as prophylaxis during IPP implantation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Xie et al reported no difference in toxicity in a comparative analysis of over 800 patients receiving low-dose (80 mg) vs weight-based dosing of gentamicin. 15 There was a higher incidence of infection in the low-dose gentamicin group (1.22% vs 0.74%), although this was not significant. The optimal dosing of gentamicin remains unclear but our series was unable to demonstrate a difference between groups.…”
Section: Discussionmentioning
confidence: 75%
“…Xie et al reported no difference in toxicity in a comparative analysis of over 800 patients receiving low-dose (80 mg) vs weight-based dosing of gentamicin. 15 There was a higher incidence of infection in the low-dose gentamicin group (1.22% vs 0.74%), although this was not significant. The optimal dosing of gentamicin remains unclear but our series was unable to demonstrate a difference between groups.…”
Section: Discussionmentioning
confidence: 75%
“…Among all the risk factors, the most important ones seem to be, without doubt, the presence of diabetes mellitus and the reintervention (defined as a change of penile prosthesis): in fact, while the incidence of infection after de novo implant is found only in 1–3% of the patients, in cases of revision surgery, the risk increases to 10% and in diabetic patients, it has even been reported to reach 18% [5]. Many of the selected articles addressed the prevention of PPI, but there is no clear consensus worldwide on certain topics, including the use of antibiotic therapy: about this topic, the 2 most relevant studies [6, 7] suggested that higher doses of gentamicin act as a protective factor; however, no significant association was found.…”
Section: Resultsmentioning
confidence: 99%
“…A recent retrospective study comparing weight-based to nonweight-based gentamicin dosing in inflatable penile prosthesis (IPP) implantation found no difference in the rate of postoperative acute kidney injury (AKI) [3]. However, the study was limited by the lack of any postoperative measures of nephrotoxicity and only evaluated rates of readmission for AKI.…”
Section: Introductionmentioning
confidence: 99%